2021
DOI: 10.3390/vaccines9010047
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Influenza

Abstract: Two reviews by Harding and Heaton [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(27 reference statements)
0
9
0
1
Order By: Relevance
“…The HA, NA and matrix proteins provide a diverse set of highly conserved influenza virus epitopes that we incorporated into our composite influenza peptide immunogens. While HA has been a focus for many seasonal vaccines, other influenza proteins such as NA and M2e have been proposed as important vaccine components to induce broad neutralizing antibodies [ 5 , 6 , 7 , 8 , 9 , 10 ]. Monoclonal antibodies to each of the peptide epitopes in the composite antigens used in this study were shown to neutralize influenza viruses across Groups 1 and 2 contemporary strains (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HA, NA and matrix proteins provide a diverse set of highly conserved influenza virus epitopes that we incorporated into our composite influenza peptide immunogens. While HA has been a focus for many seasonal vaccines, other influenza proteins such as NA and M2e have been proposed as important vaccine components to induce broad neutralizing antibodies [ 5 , 6 , 7 , 8 , 9 , 10 ]. Monoclonal antibodies to each of the peptide epitopes in the composite antigens used in this study were shown to neutralize influenza viruses across Groups 1 and 2 contemporary strains (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Immunity to influenza induced by M2e may include both innate and adaptive immune responses and therefore has been considered an important target for developing a universal influenza vaccine [ 8 , 9 ]. The HA and NA peptides are highly conserved and located near or at the protein area where the receptor binding sites reside [ 10 , 11 , 12 ]. These epitopes classically are impacted by induction of antibodies through the adaptive immune system and a major target for influenza vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in influenza vaccine technology such as cell versus egg grown vaccines, adjuvants, etc [123,124].…”
Section: Factors Increasing Ewm With Time Factors Reducing Ewm With Timementioning
confidence: 99%
“…Consequently, a number of research teams and pharma companies have carried out studies aimed at developing a universal vaccine against the influenza virus. There are different approaches to constructing a universal influenza vaccine, e.g., developing recombinant protein immunogens, using conserved influenza virus antigens (hemagglutinin stem, and proteins NP, PB1, M1, and M2), or developing new types of vaccines [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%